PENGEMBANGAN KEMAMPUAN KOGNITIF MURID SEKOLAH’DASAR MELALUI PENDIDIKAN JASMANI - Sukoco, Pamuji (Jurnal Cakrawala Pendidikan, 2016)
The elementary school students are at a stage in need of an environment conducive for their development. Physical education can enhance cognitive ability through physical activities in the learning process. The teaching learning process in Physical Education should be designed with motoric experience that develops motoric perception, drives social interaction, and stimulates cognitive ability. The learning approach should use games and stimulate problem solving. The students should get the opportunity to think logically and creatively and develop their attention and memory